2004
DOI: 10.1507/endocrj.51.97
|View full text |Cite
|
Sign up to set email alerts
|

An Aberrant ACTH-producing Ectopic Pituitary Adenoma in the Sphenoid Sinus

Abstract: Abstract.A 32-year-old woman with an ectopic adrenocorticotropic hormone (ACTH)-secreting pituitary adenoma (EAPA) is presented. She had rapidly gained weight and suffered recurrent facial acne for a few years but lacked the typical Cushingoid features. Endocrine examinations revealed that her plasma ACTH was markedly high (196 to 280 pg/ml) without showing normal circadian rhythm and failed to respond to corticotropin-releasing hormone stimulation. Her cortisol levels ranged from 22 to 30 mg/dl throughout obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Women are affected more than men [5,6]. The various clinical presentations depend on the space-occupying effect of the lesion or hormonal activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are affected more than men [5,6]. The various clinical presentations depend on the space-occupying effect of the lesion or hormonal activity.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English literature has shown, to date, fewer than 40 cases [1][2][3][4][5][6]. Furthermore, some authors think a pre-operative diagnosis of EPA is often difficult to make.…”
mentioning
confidence: 99%
“…Molecular analysis of circulating ACTH was performed by gel chromatography as previously reported [4,5]. Briefly, the plasma sample was extracted using SEP-PAK C 18 cartridge (Waters, Milford, MA).…”
Section: Analysis Of Preoperative Plasma Acth By Gel Chromatographymentioning
confidence: 99%
“…Given that the cause was a functional pituitary adenoma, this result appears to be inconsistent with the known feedback-inhibition pattern found in functional ACTH-secreting pituitary adenomas. Suzuki et al 37 performed a literature review and found a variable response to dexamethasone suppression in multiple other cases. It is likely that these tumors behave differently than central adenomas in terms of glucocorticoid suppression.…”
Section: Discussionmentioning
confidence: 99%